Comparative growth and survival of spat of the Caribbean pearl oyster, Pinctada imbricata cultivated indoor with microalgae diets and outdoor with natural diet. (5th April 2016) - Lodeiros, C.J.; Freites, L.; Márquez, A.; Glem, M.E.; Guevara, M.; Saucedo, P.E.
Abstract: We report the results of survival and growth in size and dry mass of spat of the Caribbean pearl oyster Pinctada imbricata cultivated under outdoor (field culture) and indoor (Laboratory) conditions. Field group fed on environmental seston. Laboratory groups were fed with mono, binary and ternary mixtures of three cultivated algae: Isochrysis galbana (Ig), Tetraselmis chuii (Ig) and the Chaetoceros sp. (Ch‐A, isolated from north‐eastern Venezuela). After 30 days of trial, fatty acid profiles of spat were determined along with growth in length and height shell, adductor muscle and soft tissue dry mass. During the field grow‐out phase (field culture), samplings were performed at days 1, 15 and 30 to measure environmental variables of phytoplankton biomass (chlorophyll a ), dissolved oxygen, seston, temperature and salinity. A significant increase in size and soft tissue mass occurred in spat fed the diets including the tropical diatom ( Chaetoceros sp.). In contrast, monoalgal diets of Tc and Ig yielded no significant differences in size and mass of spat, compared with the field culture. These results suggest that nutritional requirements of cultivated spat for specific fatty acids of physiological importance for marine bivalves, such as: 16:0, 16:1n‐7, 18:2n‐6, 20:4n‐6, 18:3n‐3 and 20:5n‐3, were satisfied from microalgal diets with Ch‐A, alone or in combination, compared with spat fed from the field culture.